Effects of Computer Assisted Instruction with Animation of Biology Students’ Achievement in Niger State (Post Covid-19 Remedy for Teaching and Learning) - Kuta; Tukura; Yahaya Fatima; Ali Fati; A, Ndatsu (Ceddi Journal of Education, 2024)
This study investigates the effects of Computer Assisted Instruction (CAI) with animation on biology students' achievement in Niger State, serving as a post-COVID-19 remedy for teaching and learning. The research employed an experimental design with Senior Secondary II (SSII) students as the target population. Schools and class groups were selected using random sampling, and each group (experimental and control) consisted of thirty students, equally distributed by gender (15 males and 15 females). A reliability coefficient of 0.75 was determined using the PPMC formula. Analysis of Variance (ANOVA) was employed to test hypotheses, leading to the rejection of the first null hypothesis and retention of the second. Results indicate that integrating teaching and learning aids, particularly CAI with animation, alongside conventional methods, significantly improves student achievement in biology. The study recommends widespread adoption of CAI with animation software in all Senior Secondary Schools to enhance academic performance in Biology. This approach addresses the challenges posed by traditional teaching methods, especially in the context of adapting to post-pandemic educational needs.